Purification and Characterization of Phytase from Fruit Bodies of Local mushroom Pleorotus ostreatus Grown by Solid State Fermentation - Abdullah A. Hassan; HawazinA.Al-Jobory (Tikrit Journal of Pure Science)
Phytase produced from an edible local mushroom P.ostreatus11L was purified in three steps, in precipitation with ammonium Sulfate (saturation ratio70%), the specific activity of phytase increased from 0.38u/mg protein in crude extract to 0.77 u/mg protein with purification of 2.03 fold and  the enzyme yield was 92.05%, in ion exchange chromatography(DEAE-cellulose) step, specific activity was 3.6 u/mg protein with purification of 9.47 fold  with a yield of 71. 82%. In the last step, with gel filtration chromatography using Sephadex G75 which gave the highest specific activity reached 7.5 U/mg with the purification folds arrived to 19.74 and enzyme yield was 42.61%. The results showed that there is only one band appeared in SDS-PAGE technique indicating a high purity of phytase enzyme , the purified phytase behaved as a monomeric protein with a molecular mass of about 25.12 kDa . The phytase was active over a broad range of incubation temperature (20 - 50ºC), maximal activity was 0.83 unit/ml when phytase incubated at 30ºC while the enzyme has thermal stability over a broad range of temperatures (20-60ºC) for one h since more than 50 % of the relative enzyme activity was retained after incubation. Phytase was active over a broad range of pH (4-8), maximal activity was 0.81unit/ml when phytase incubated at pH 6 followed by 0.79 unit/ml when phytase incubated at pH 5 without significant differences between them. In addition , the enzyme was full stable at pH 5 and 6 for 1 h of incubation at 37oC. phytase activity didn’t reach 70% at the other pH values. Hence it is inferred that the phytase was active over a broad range of  pH 4-8. Among various metal ions, only MgSO4 has a syregenic effect with phytase activity in which activity increased as residual activity was 117.36% , while CuSO4 and ZnCl were the most inhibitory agents for P.ostreatus phytase.